Analisis Indeks Komponen Hambatan Masuk Pasar dan Indeks Fungsi dalam Mengukur Daya Saing Pasar - Kharisma Bintang Maulana Tibridzi; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article is made to learn the definition, components, and calculation formula of the Market Entry Barriers Component Index and Function Index, where these two measuring instruments are very important in analyzing the market. The function of the Market Entry Barriers Component Index is to evaluate the level of difficulty that a company will face in entering a pre-existing market. The way to evaluate it is by looking at obstacles such as fixed costs, production capacity, regulation, and production. For the Function Index itself, it functions to see how much efficiency will occur and includes distribution, information flow, and market mobility. This article also aims to provide an example of how the calculation system for the two indexes works. Through this understanding, readers and companies can formulate more appropriate strategies in dealing with obstacles and taking advantage of opportunities in the market.